MODERN APPROACHES TO THERAPY FOR CHILDREN WITH MUCOPOLYSACCHARIDOSIS - N. V. Buchinskaya; I. А. Chikova; E. А. Isupova; О. V. Kalashnikova; М. М. Kostik; V. G. Chasnyk ("Paediatrician" Publishers LLC, 2014)
Mucopolysaccharidosis is the group of hereditary metabolic disorders; it is characterized by accumulation of glycosaminoglycans owing to storage of specific lysosomal enzymes. Background: Research objective was to study the influence of enzyme replacement therapy on a somatic state and psychomotor development of children with mucopolysaccharidosis type I and II of various severity in dynamics and to estimate its efficiency. Patients and methods: The data of five years' supervision over 13 patients with mucopolysaccharidosis type I and II is used in the research. During the work the therapy efficiency analysis is made by the following criteria: data of objective examinations, ultrasound investigation of liver, spleen and heart, quantitative determination of excretion of urine glycosaminoglycans, assessment of articular and abarticular affection by JADI scale, assessment of social age and social coefficient by Doll's scale. Results: The reliable distinctions in the contents of urine glycosaminoglycans and also by results of an objective assessment of the liver and spleen sizes and of ultrasonic research of the spleen area in 6 and 12 months of treatment in comparison with basic data are received. The reliable decrease in social coefficient indicator at the first stage of therapy is registered, and then distinctions have insignificant character. There was no essential dynamics of the articular status on treatment that is connected with process stabilization. There are no reliable evidences of both positive and negative dynamics on myocardium involvement, ultrasonic characteristics of the sizes of hepatic lobes. Conclusion: Enzyme replacement therapy is an effective method of treatment of somatic manifestations of various types of mucopolysaccharidosis.